The use of historical courtyards for musical performances. Issue 3 (September 2016) - Iannace, Gino
This work reports the measurements of the acoustic characteristics carried out in three historic courtyards set up for musical performances. Even if the courtyards are not necessarily suitable locations for musical events, due to organizational reasons, with it being possible to control the audience, along with the suggestiveness of the places, they are chosen by the organizers and are highly popular and appreciated by both musicians and singers alike. The acoustical problems are due to the absence of the ceiling, which does not re-send the sound into the room, as well as the flat and parallel walls that generate unwanted multiple reflections. The acoustic study of the courtyards was carried out according to the standard ISO 3382 by placing a sound source on the stage where the musicians sit and the microphone receivers in the courtyard in the absence of the audience. Furthermore, the spatial distribution of the acoustic parameters in the presence of the audience was evaluated using architectural acoustics software.